Identification of plant resistance inducers and evaluation of genotype receptivity for carrot protection against Alternaria leaf blight - Le Clerc, Valérie; Moussa, Sitti Anlati; Suel, Anita; Koutouan, Claude Emmanuel; El Ghaziri, Angelina; Gaucher, Matthieu; Brisset, Marie-Noelle; Briard, Mathilde; Geoffriau, Emmanuel (Frontiers in Plant Science, 2025)
The use of biopesticides represents an alternative strategy to synthetic chemical products for crop protection. To promote their adoption and effective use by growers, it is crucial to understand their modes of action and the optimal conditions for their application in crops, including their compatibility with specific varieties. Through a series of greenhouse experiments, this study describes the development and validation of a robust molecular diagnostic tool for enabling the evaluation of defence gene activation. The results identified plant resistance inducers (PRIs) among biopesticide products capable of protecting carrots against Alternaria leaf blight. By applying a PRI to a range of carrot varieties exhibiting varying levels of resistance to Alternaria dauci, preliminary findings on plant receptivity suggest that the efficacy of PRIs in conferring protection is highly dependent on the treated variety. Two distinct genotype-dependent effects were observed: sensitivity to the PRI and an enhancement of resistance. This study offers new insights into optimising biopesticide use in carrot cultivation.